ANALYSIS OF THE APPLICATION OF THE LINEAR PROGRAMMING SIMPLEX METHOD IN ES KUL – KUL - Yusnita, Erli; Utomo, Pradita Eko Prasetyo (Nindikayla Institute, 2024)
This study aims to analyze the application of the Simplex method in Linear Programming to optimize the production and sales of Es Kul-Kul. Es Kul-Kul is a cold drink product that is currently in great demand by the public, especially in summer. However, in the production process, there are often obstacles such as limited raw materials, production time, and labor capacity, which affect efficiency and profits. Therefore, a method is needed that can help determine the best combination of these factors so that maximum profits can be achieved. The Simplex method is used in this study as a mathematical tool to solve optimization problems. The objective function in this study is to maximize profits from the sale of Es Kul-Kul, taking into account various constraints, such as the amount of raw materials available, production time per unit, and daily labor capacity. The data used was obtained from the production and sales records of Es Kul-Kul during a certain period. The results show that the Simplex method can help identify optimal solutions in the allocation of limited resources. By implementing optimization results, Es Kul-Kul is able to increase production efficiency and obtain greater profits without the need to add new resources. This research provides practical benefits for small and medium enterprises (MSMEs) in managing production and increasing profits in a measurable manner